2020
DOI: 10.1016/j.xnsj.2020.100011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiological and functional results of transforaminal lumbar interbody fusion in degenerative spondylolisthesis

Abstract: Purpose To evaluate the clinical, functional and radiographic outcomes of transforaminal lumbar interbody fusion (TLIF) in degenerative low-grade spondylolisthesis. Materials and Methods A prospective observational study of 120 consecutive patients (M: F = 24:96) with spondylolisthesis operated with TLIF. Clinical and functional outcome was assessed on Visual analogue Scale (VAS) and Oswestry Disability Index(ODI). The radiological outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Tất cả các bệnh nhân đều đau cột sống thắt lưng và đau kiểu rễ thần kinh, trong đó ghi nhận 19 trường hợp có biểu hiện đi cách hồi thần kinh. Kết quả này tương đồng với các tác giả trong và ngoài nước như Võ Văn Thành, Kakadiya D. G. [6], [2], [7]. Đây là triệu chứng gây ảnh hưởng đến sinh hoạt và đời sống, bắt buộc bệnh nhân phải đến viện khám và điều trị.…”
Section: đặC đIểm Lâm Sàng Và Hình ảNh Họcunclassified
“…Tất cả các bệnh nhân đều đau cột sống thắt lưng và đau kiểu rễ thần kinh, trong đó ghi nhận 19 trường hợp có biểu hiện đi cách hồi thần kinh. Kết quả này tương đồng với các tác giả trong và ngoài nước như Võ Văn Thành, Kakadiya D. G. [6], [2], [7]. Đây là triệu chứng gây ảnh hưởng đến sinh hoạt và đời sống, bắt buộc bệnh nhân phải đến viện khám và điều trị.…”
Section: đặC đIểm Lâm Sàng Và Hình ảNh Họcunclassified
“…During the surgery, indirect foraminal decompression of the neural elements is achieved, as the intervertebral disc is replaced with an intervertebral implant and bone graft, restoring proper intervertebral space and height, with subsequent posterolateral pedicle fixation for immediate construct stabilization [14,15]. The clinical results of successful fusion are depicted in alleviated post-operative pain scores and regained daily function [16]. As such, Kakadiya et al, reporting data from 120 patients following TLIF surgery, demonstrated approximately 70% pain reduction in the visual analogue scale (VAS) score and over 60% reduction in the Oswestry Disability index (ODI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical results of successful fusion are depicted in alleviated post-operative pain scores and regained daily function [16]. As such, Kakadiya et al, reporting data from 120 patients following TLIF surgery, demonstrated approximately 70% pain reduction in the visual analogue scale (VAS) score and over 60% reduction in the Oswestry Disability index (ODI) [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The historical target was "as much lordosis as possible." This continued until several authors, including Schwab et al and Lafage et al, proposed matching PI to LL within 10°, which has been shown to improve outcomes even in surgical procedures for degenerative pathology 35,[40][41][42][43][44][45][46][47][48][49][50][51] . It has been suggested to correct LL to PI 1 10°if the PI is low and to PI 2 10°if the PI is high 52 .…”
mentioning
confidence: 99%